Greek Education in the United States - Nikolidakis, Nikos (Études helléniques / Hellenic Studies, 2005)
This detailed portrait of the American situation presents the poignant history of Greek immigration. The author focuses on various community efforts to sustain language and culture among the children of immigrants and subsequent generations. He underscores the level of organization involved in the early years as well as the perceived role of the Orthodox church. Overall the article presents well-documented figures and points to a hopeful future for Greek language learning despite a decrease in student populations.